Implementasi Buy Back Guarantee Dalam Perjanjian Kerjasama Antara Bank Dengan Supplier Terkait Penyaluran Pembiayaan Mesin (Studi Pada PT. BPRS XXX Bekasi) - Adham - (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
The buy back guarantee agreement in the cooperation agreement aims to protect the bank frombusiness risks in the distribution of machine ownership financing. Buy back guarantee is defined asthe ability of the supplier as a guarantor against the bank, to "buy back" the machine object afterthe debtor is declared in default to the bank. Based on the description, the writer tries to examine theimplementation of the buy back guarantee agreement related to the distribution of machine financing,and legal remedies for the bank applying the contents of the buy back guarantee if there is default onthe debtor. The research method used in this research is normative juridical with analytical descriptivespecifications.The research was carried out through literature study, then looked at the relationshipbetween one law and another and carried out an analysis related to the application of its practice.After getting a description of the research results, the writer analyzes and draws conclusions fromthe research results obtained. Primary data collection is also carried out to support secondary data,which is obtained by documentation and bank interviews related to the machine ownership agreement.The results of the study concluded that the implementation of the buy back guarantee was carriedout in several stages, namely the stage of the debtor's statement of default, the negotiation stage,and the stage of the agreement, the application of the buy back guarantee. Apart from that, the buyback guarantee that applies to PT. BPRS XXX Bekasi, there are two types of definitions: "buy backguarantee" and "help resell" by the supplier. Legal action has never been taken by the bank whenthere is default from the debtor. The bank is more concerned about the good ethics of the supplier tobuy / help sell the machine goods. The suggestions that the writer can give include, banks must applyprudential banking principles more selectively, suppliers do not only pursue sales targets but payattention to the side of the bank so that cooperation remains well established. n addition, research isneeded regarding the perspectives of the bank, supplier and debtor in addressing the problems thatexist in buy back guarantee in more depth and breadth.